Review of Various Transmission Loss Allocation Methods: A Case Study of Integrated Nepal Power System using Best Method - Gurung, Suraj; Gautam, Basanta Kumar (Himalayan Journal of Applied Science and Engineering, 2022)
This paper presents a review of the most relevant and practical methods for allocating transmission loss in a deregulated market. They are the pro-rata (PR) method, the marginal allocation (ITL) method, the proportional sharing (PS) method, and the Z-Bus method. This study has also performed a qualitative comparison of four methods using the IEEE 14 bus system. Finally, the Z-Bus method is selected as the best option for implementation in the Integrated Nepalese Power System Network (INPS). As of 2022, the loss allocation is determined at all 132 and 220 kV substations of INPS. The study of transmission loss allocation for INPS is carried out for six different cases, considering the variation in patterns of energy generation and demand, i.e., system full generation, summer peak, winter peak, average peak, dry peak, and contingency condition. The result shows the load, like Kathmandu Valley, which is in the region of generation, and the generator, like in the eastern region, which is in the region of demand, are mostly compensated with negative losses. Loads in the western region and generators like the Upper Tamakhoshi, which are far from the generator or load, are assigned the highest positive loss. Loss allocation to load and generator can vary depending on the loading conditions that INPS is operating under. The generation is comparably distributed in the full generation, summer, and contingency instances; as a result, the loss allocation to both loads and generators is significant. However, the bulk of losses are only attributed to the generator side in the three other scenarios with less generation, when the majority of the generation is only aggregated in a specific location. This is a result of the remote generator's long-distance power flow, which raises system loss. As a result, the Z-Bus method assigned the generator side the majority of the losses. Additionally, the majority of INPS's generation is determined to be remotely located, which increases their risk of transmission loss. Because of this, INPS is best served by the Z-Bus approach, which takes into account the locations of buses within the network. In order to minimize system loss, this encourages big demand or generation to be positioned close to the center of generation or demand.